Words that Burn: On the Manners and Implications of Oath-Taking Practices in Ethiopian Amhara Customary Law, Nineteenth–Twentieth Centuries - Ficquet, Éloi (Aethiopica, 2020)
Between the spoken word, ritual action, and legal processes, the studies of oath-taking practices have developed a broad literature. This article provides an additional layer of materials and analysis on speech acts and ritual procedures involved in the manners of taking an oath in the Christian societies of Ethiopia, as recorded from the midnineteenth century to the early twentieth century. Some samples of Amharic discourse specific to the manners of oath-taking in the customary legal system of Christian Ethiopia are presented here through extracts from unpublished field notes recorded in the 1840s by the French traveller Arnauld d’Abbadie. This source is then compared to other ethnographic observations of oath-taking statements and rituals in the context of Ethiopian Christian societies. The implications of swearing an oath in Ethiopian customary law lead to the critical re-examination of the history of Ethiopian law in a comparative outlook, particularly with the canonical laws of Eastern and Western Europe.